Michelet - Barthes, Roland 1915-1980; Geble, Peter (Frankfurt am Main Europäische Verlagsanstalt, 1980)
Published in France in 1954, Roland Barthes's Michelet inspired a revival of interest in the great 19th century French historian. Neither a biography nor a critique, Michelet is Barthes's effort to give the reader a sense of the whole man.
Jules Michelet (1798-1874) was a French historian and an author on other topics whose major work was a history of France and its culture.
Keywords: Michelet, Jules -- 1798-1874; Philosophy; Semiotics; History